Clusterin facilitates glioma progression via BCL2L1-dependent regulation of apoptotic resistance - Xu, Qingqing; Liu, Xin; Zhang, Yibo; Yuan, Shiyu; Huang, Wenli; Pi, Mingshan; Xiong, Qi; Zhou, Hongyan; Gui, Yuran; Xiao, Yifan; Wang, Xiaochuan; Shu, Xiji; et al. (Frontiers in Molecular Neuroscience, 2025)
BackgroundClusterin (CLU) is a multifunctional protein involved in various pathophysiological processes and diseases. Glioma, the most common aggressive primary brain tumor, is characterized by high morbidity, mortality, and extremely poor prognosis. Our research has found that CLU is upregulated in glioma and contributes to increased tumor malignancy. However, the specific regulatory mechanisms of CLU in the context of glioma are not fully understood.MethodsWe used glioma public databases, immunohistochemistry (IHC), and immunoblotting techniques to evaluate the expression levels and prognostic value of CLU in glioma. Cell migration and proliferation assays, including the scratch wound healing and MTT assays, were conducted to assess the functional impact of CLU. In addition, immunoblotting and flow cytometry were used to analyze apoptosis-related proteins and CLU-BCL2L1 interactions. An in situ tumor model using nude mice was established to investigate the effects of CLU in vivo.ResultsBioinformatics analyses showed that CLU was highly expressed in glioma, associated with poor clinical outcomes. Functional assays revealed that CLU and BCL2L1 promoted glioma cell migration and proliferation. Silencing CLU reduced the migration and proliferation of glioma cells, while overexpression of CLU enhanced these aggressive phenotypes. Mechanistic studies showed CLU regulated BCL2L1 expression, inhibiting apoptosis pathways and promoting malignancy. In vivo experiments confirmed the inhibitory effects of CLU downregulation on glioma growth.ConclusionThis study clarifies the role of the CLU-BCL2L1 axis in promoting glioma migration and proliferation both in vitro and in vivo. It suggests that targeting this pathway may be a promising therapeutic strategy for glioma.